2015
DOI: 10.1167/15.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Linking perceptual learning with identical stimuli to imagery perceptual learning

Abstract: Perceptual learning is usually thought to be exclusively driven by the stimuli presented during training (and the underlying synaptic learning rules). In some way, we are slaves of our visual experiences. However, learning can occur even when no stimuli are presented at all. For example, Gabor contrast detection improves when only a blank screen is presented and observers are asked to imagine Gabor patches. Likewise, performance improves when observers are asked to imagine the nonexisting central line of a bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In a similar manner, high-level processes can generate low-level percepts through visual imagery. Visual imagery can lead to the formation of phantom-like percepts that can bias future perception 39 and even lead to visual perceptual learning 40 . Besides visual imagery, phantom percepts such as observed in the filling-in phenomenon were shown to generate neural activity in the early visual cortex 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, high-level processes can generate low-level percepts through visual imagery. Visual imagery can lead to the formation of phantom-like percepts that can bias future perception 39 and even lead to visual perceptual learning 40 . Besides visual imagery, phantom percepts such as observed in the filling-in phenomenon were shown to generate neural activity in the early visual cortex 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar processes occur in mental imagery, where high-level processes generate activations in low-level neurons, giving rise to phantom-like percepts ( Pearson, Clifford, & Tong, 2008 ). Hence, visual imagery can lead to the formation of phantom-like percepts that can bias future perception ( Pearson et al, 2008 ; Sterzer, Frith, & Petrovic, 2010 ) and even replace the real visual stimulus and lead to visual perceptual learning ( Grzeczkowski, Tartaglia, Mast, & Herzog, 2015 ; Shibata, Watanabe, Sasaki, & Kawato, 2011 ; Tartaglia, Bamert, Mast, & Herzog, 2009 ). Accordingly, it was shown that stimulus-driven and imagery-driven representations have overlapping neural topography and induce similar activations in early visual areas that are retinotopically organized and feature specific ( Naselaris, Olman, Stansbury, Ugurbil, & Gallant, 2015 ; Slotnick, Thompson, & Kosslyn, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the pathways corresponding to both types of codes co-evolved to predict how real objects behave in the immediate future, to avoid attackers or catch prey [92][93][94], and to select and guide the most adaptive among many available actions [13,[95][96][97]. Along this line of research, evidence supporting the claim that imagery has a facilitatory role in prediction is provided by the findings that, similar to the effects of perceptual learning and practice, that imagery increases sensitivity in hyperacuity (i.e., gap detection) when the same stimulus is visualized repeatedly over a block of trials [98,99]. This further validates the finding that visual imagery can shape low-level sensory representation.…”
Section: The Interaction Between Visual Mental Imagery and Visuospatial Perceptionmentioning
confidence: 99%